Evaluation of Steel Stairwell Dynamic Characteristics, Under Few Mass Configurations Using Ambient Vibration Method - Kamarudin, Ahmad Fahmy (International Journal of Integrated Engineering, 2019)
Application of external mass on existing emergency steel stairwell in this study has altered the natural frequency when the resonance threshold has been reached and allows disruption to the human comfort feeling. Ambient vibration testing and modal analysis were carried out on 6 meter height of emergency steel stairway portal frame by using 1 Hz of tri-axial seismometer sensor and open source software of GEOPSY as the processing tool. The stairwell platforms were subjected by cumulative ascending static mass configurations of 300 kg, 600 kg and 900 kg. Identification of the predominant first mode frequency, f1, and mode shapes were made with specified empirical filtering protocols were applied. Fourier Amplitude Spectra (FAS) was used to transform the ambient vibration time series, when the first predominant frequency under bare frame (BF) condition shows at 8.32 Hz. f1 decreased linearly to 7.35 Hz (BF+300kg), 6.77 Hz (BF+600kg) and 6.23 Hz (BF+900 kg), when the masses were increased. In addition, at these frequencies’ ranges, bad human subjective experiences could be triggered as recommended by previous researchers between 8 to 5 Hz. Besides, the deflection shapes from the first mode frequency was also illustrated at higher deflection amplitude to one of the portal frame’s column which resisting two stairwell platforms. These amplitudes are higher when f1 is decreasing. It can be concluded that, ambient vibration approach has efficiently evaluated the dynamic characteristics and its influence against the structure-person interaction on existing steel stairwell portal frame in this study. Further strengthening work on the steel frame could decrease the reductions percentages of the predominant frequencies, deflection amplitudes and even increase the human comfort level when using the stairwell, especially during building evacuation procedure.